ANALISIS PROFIL DAN KEPUASAN KONSUMEN ABON DAGING SAPI DI KOTA PALU - Marhaeni, Marhaeni (FAPETKAN UNTAD, 2014)
Palu City is an area that has great potential in the field of animal husbandry, particularly when focused on the processing of livestock products such as shredded beef or other meat.The purpose of this study was to analyze the profile and customer satisfaction to shredded beef.This research was conducted on consumers who consume shredded beef products produced by three of the nine producers in the city of Palu. The analytical method used is descriptive analysis and factor analysis.The results showed that (1) the consumer profile shredded beef in Palu, the majority of consumers are women, mostly housewives, the majority of productive age 20-29 years,the majority of high school educated/ equivalent, and come from all corners of the lower classes either,middle and upper. (2) The level of consumer satisfaction seen from product attributes indicate consumers are satisfied views of product quality attributes shredded beef. Keywords : Profile, consumer’s profile and satisfaction, shredded beef.